# Maths Wiz Solutions Class 8 Chapter 5

## Maths Wiz Class 8 Solutions Chapter 5 Algebraic Expressions

Welcome to NCTB Solutions. Here with this post we are going to help 8th class students for the Solutions of Maths Wiz Class 8 Math Book, Chapter 5, Algebraic Expressions. Here students can easily find step by step solutions of all the problems for Algebraic Expressions, Exercise 5A, 5B, 5C, 5D, 5E, 5F, 5G and 5H Also here our mathematics teacher’s are solved all the problems with easily understandable methods with proper guidance so that all the students can understand easily. Here in this post students will get chapter 5 solutions. Here in this post all the solutions are based on ICSE latest Syllabus.

Algebraic Expressions Exercise 5A Solution :

Question no – (1)

Solution :

(a) 5x2 – 3x + 1 is a polynomial

(b) 3√x – 5x – 11 is not a polynomial

(c) √3x3 + 8 is a polynomial

(d) 2m-1 + m + 1 is not a polynomial

(e) 5x is polynomial

(f) 59 = 59x° is a polynomial

(g) x/2 + 3 is a polynomial

(h) 9/x – 2x2 + 13 is not a polynomial

(i) 3/2x + 1 is not a polynomial

(j) πx2 – 2 is a polynomial

Question no – (2)

Solution :

(a) 2p2 + 5p3 + p

= It is a trinomial with coefficients 2, 5, 1 and degree is 3

(b) 7a2 + 5a + (-7) a4

= It is a trinomial with coefficients 7, 5, (-7) and degree is 4

(c) a2 – b2

= It is a binomial with coff 1, -1

(d) 8x5 + 3x3y – 2x2y2 + y6

= It is neither with coff, 8, 3, -2, 1 degree – 6

(e) – 18x6

= It is monomial with coff – 18, degree -6

(f) xy + yz + zx

= trinomial coff 1, 1, 1 degree 2

Question no – (3)

Solution :

(a) ab, 3ab and ac, 3ac

(b) 3xy, 5xy and xz, -7xz

(c) -8, + 5 and x2y, + 3x2y

(d) ab, 4ab and 2a2b2, 3a2b2

(e) None

(f) 23x2y, 25x2y, -3x2y

Question no – (4)

Solution :

(a) 15b + 8b

= 23b  …(Simplified)

(b) 7p – p + 21p – 8p

= 21p – p – p

= 19p …(Simplified)

(c) 5x2 + 8x + 7 + 9x2 – 2x – 12

= 14x2 + 6x – 5 …(Simplified)

(d) 59 + 20y4 + 30y4

= 50y4 + 59 …(Simplified)

(e) (7x+ 5x2 + 3x + 8) + (9x3 – 2x2 + 9 – 7x)

= (7x3 + 9x3) + (5x2 – 2x2) + (3x – 7x) + (8 + 9)

= 16x3 + 3x2 – 4x + 17 …(Simplified)

Question no – (5)

Solution :

(a) 3x + 4

7x – 1
———————-
10x + 3

The sum will be 10x + 3

(b) 3y2 + 4y – 7

y2 + y + 12
———————-
4y2 + 5y + 5

The sum will be 4y2 + 5y + 5

(c) x4 – x2y + 3y2

– x4 + 2x2y + y2
———————-
x2y + 4y2

The sum will be x2y + 4y2

Question no – (6)

Solution :

(a) As per the question,

7y² + 5x²

2y² – 3x²

——————————
5y² + 8x²

(b) As per the question,

5ab + 6bc – 7ca

– 2ab + 4bc + 2ca
——————————
7ab + 2bc – 9ca

(c) As per the question,

4a – 3b – 9c

– 2a – 5b – 10c
——————————
6a + 2b + c

Question no – (7)

Solution :

Sum of the polynomial

(i) (-5x + 9) + (2x + 3)

= (2x – 5x) + (9 + 3)

= – 3x + 12

Difference of the polynomial

(i) – (2x – 3) + (-5x + 9)

= (-2x – 5x) + (3 + 9)

= – 7x + 12

Sum of the polynomial

(ii) (7q + p) + (q – p)

= 89

Difference of the polynomial

(ii) – (q – p) + (7q + p)

= + 6q + 2p

Sum of the polynomial

(iii) (y4 – 9) + (y4 + 3)

= 2y4 – 6

Difference of the polynomial

(iii) – (y4 + 3) + (y4 – 9)

= – 12

Sum of the polynomial

(iv) (5m2 + 3m + 8) + (6m2 + 2m + 10)

= 11m2 + 5m + 18

Difference of the polynomial

(iv) – (6m2 + 2m + 10) + (5m2 + 3m + 8)

= – m2 + m – 2

Sum of the polynomial

(v) (x2 – xy – y2) + (- x2 + xy – y2)

= – 2y2

Difference of the polynomial

(v) – (-x+ xy – y2) + (x2 – xy – y2)

= + 2x2 – 2xy

Sum of the polynomial

(vi) (3m2 – 5mn + 7n2) + (2mn – 5n2 – m2)

= 2m2 – 3mn + 2n2

Difference of the polynomial

(vi) – (2mn – 5n2 – m2) + (3m2 – 5mn + 7n2)

= – 7mn + 6mn – 10n2

Question no – (8)

Solution :

(a) (5m2 – 4n2) – (-5m2 + 6mn + 6n2)

= 10m2 – 6mn – 10n2

(b) (a2 + 2ab – b2) – (4a2 – 2ab + 4b2)

= -3a2 + 4ab – 5b2

Question no – (9)

Solution :

Given, (3x2 + 5x + 4) + (x2 + 6) – (3 – 7x)

= (3x2 + x2) + (5x + 7x) + (4 – 3)

= 4x2 + 12x + 1   …(Simplified)

Question no – (10)

Solution :

Given, (x2 + y2 – z2) – (3z2 – 2x2 – 4y2) + (4y2 + x2 + z2)

= (x2 + 2x2 + x2) + (y2 + 4y2 + 4y2) – (z2 + 3z2 + z2)

= 4x2 + 9x2 – 4z2     …(Simplified)

Algebraic Expressions Exercise 5B Solution :

Question no – (1)

Solution :

(a) 5 × 2x

= 10x

∴ Product will be 10x

(b) (-3y × 4y)

= -12y2

Product will be -12y2

(c) (-6p) × (-8pqr)

= 48p2qr

Product will be 48p2qr

(d) (12p5) × (-5p)

= – 60p6

Product will be -60p6

Question no – (2)

Solution :

Given, length is = 6x3y2

As we know that, Area of rectangle

= (Length x Breadth) square units.

Now Area of rectangle,

= (6x2y2 × 3xy2)

= 18x3y4

Therefore, the Area of rectangle will be 18x3y4

Area of rectangle : Question no – (3)

Solution :

(a) 3y3 × (-3y2)

= -9y3+2

= – 9y5

(b) (-8x5) × 2x

= -16x5+1

= – 16x6

(c) (-4m2n) × (-3mn2)

= 12m(2+1) n(1+2)

= 12m3n3

(d) x4 × x3 × x

= x4 + 3 + 1

= x8

(e) (-4a) × (5ab) × 3b

= -60 a(1+1) b(1+1)

= – 60a2b2

(f) (-x3y2) (xy) (2y)

= – 2x(3+1) y(2+1+1)

= – 2x4y4

(g) (-1/3 a3) × (9a) × (-2a4)

= 9 × 2/3 a(3+1+4)

= 6a8

(h) (-q)3 × (2q)2

= -q3 × 4q2

= – 4q3+2

= – 4q5

(i) (2x)2 × (3x)3

= 4x2 × 9x3

= 36x2+3

= 36x5

(j) (-4z) × (-5x2)3

= (-4z) × (-125z6)

= 500z1+6

= 500z7

(k) (-3y)2 × (-3y)3

= + 9y2 × (-27y3)

= -243 y2+3

= -243y5

(l) (-0.5a2b) × (-2ab)3

= (- 5/10 a2b) × (-4a3b3)

= + 4/2 a(2+3) b(1+3)

= 2a5b4

Question no – (4)

Solution :

(a) (4a3b2) × (3a3b4) + (2ab)6

= 12a6b6 + 64a6b6

= 76a(6+6) b(6+6)

= 76 a12b12

(b) (4x3) × (2x)4 – (7x)2 (3x)5

= 4x3 × 16x4 – 49x× 3x5

= 64x7 – 147x7

= – 83x7

(c) 5p2 (-2q) (3q) + (7p2) (2q2) + (-3p) (-5p) (4q2)

= -30p2q2 + 14p2q2 + 60p2q2

= 44p2q2

(d) (-3xyz) × (4x2yz) – (5y2) (2xz2) (-x2)

= – 12x3y2z2 + 10x3y2z2

= – 2x3y2z2

Algebraic Expressions Exercise 5C Solution :

Question no – (1)

Solution :

(a) – 4 (2y + 7)

= -8y – 28

The product will be -8y – 28

(b) – 1(3x – y)

= – 3x + y

The product will be – 3x + y

(c) x2 (x – 4)

= x3 – 4x2

The product will be x3 – 4x2

(d) 3y2 (5y3 + 1)

= 15y5 + 3y2

The product will be 15y5 + 3y2

Question no – (2)

Solution :

(a) -4 (2y + 7)

= -8y – 28

The product will be -8y – 28

(b) -1(3x – y)

= -3x + y

The product will be -3x + y

(c) x2 (x – 4)

= x3 – 4x2

The product will be x3 – 4x2

(d) 3y2 (5y3 + 1)

= 15y5 + 3y2

The product will be 15y5 + 3y2

(e) -2p (p2 – p – 7)

= – 2p3 + 2p2 + 14p

The product will be  – 2p3 + 2p2 + 14p

(f) (x2 – x – 10) (-3x)

= -3x3 + 3x2 + 30x

= -2p3 + 2p2 + 14p

The product will be -2p3 + 2p2 + 14p

Question no – (2)

Solution :

(a) (6 – 5m – m7) (- 2m2)

= -12m2 + 10m3 + 2m9

The product will be -12m2 + 10m3 + 2m9

(b) y4(y7 – 3y2 + 6)

= y11 – 3y6 + 6y4

The product will be y11 – 3y6 + 6y4

(c) 3 – q + 4q3) (- q4)

= – 3q4 + q5 – 4q7

The product will be – 3q4 + q5 – 4q7

(d) – 2x2 (3x2 – 4xy + y2)

= – 6x4 + 8x3y – 2x2y2

The product will be – 6x4 + 8x3y – 2x2y2

(e) 5a3b2 (7 – 2ab4 + 3a2b5)

= 35a3b2 – 10a4b6 + 15a5b7

The product will be 35a3b2 – 10a4b6 + 15a5b7

Algebraic Expressions Exercise 5D Solution :

Question no – (1)

Solution :

(a) (y – 6) (2y + 7)

= y(2y + 7) – 6(2y + 7)

= 2y2 + 7y – 12y + 42

= 2y2 – 5y + 42

The product will be 2y2 – 5y + 42

(b) (3x – 7) (5x – 8)

= 3x (5x – 8) – 7 (5x – 8)

= 15x2 – 24x – 35x + 56

= 15x2 – 59x + 56

The product will be 15x2 – 59x + 56

(c) (x – 2) (6x + 9)

= x (6x + 9) – 2 (6x + 9)

= 6x2 + 9x – 12x – 18

= 6x2 – 3x – 18

The product will be 6x2 – 3x – 18

(d) (3m2 – n) (m2 – 2n)

= 3m2 (m2 – 2n) – n (m2 – 2n)

= 3m4 – 6m2n – nm2 + 2n2

The product will be 3m4 – 6m2n – nm2 + 2n2

(e) (3a – b2) (2a + 7b2)

= 3a (2a + 7b2) – b2 (2a + 7b2)

= 6a2 + 21ab2 – 2b2a – 7b4

The product will be 6a2 + 21ab2 – 2b2a – 7b4

(f) (x2 – 2xy) (3xy + y2)

= x2 (3xy + y2) – 2xy (3xy + y2)

= 3x3y + x2y – 6x2y2 – 2xy3

The product will be 3x3y + x2y – 6x2y2 – 2xy3

Question no – (2)

Solution :

(a) (x – 2) (x2 – 3x + 2)

= x(x2 – 3x + 2) – 2 (x2 – 3x + 2)

= x3 – 3x2 + 2x – 2x2 + 6x – 4

= x3 – 5x2 + 8x – 4

The product will be x3 – 5x2 + 8x – 4

(b) (3x + 4) (x2 – 5x + 2)

= 3x3 – 15x2 + 6x + 4x2 – 20x + 8

= 3x– 11x2 – 14x + 8

The product will be 3x– 11x2 – 14x + 8

(c) (3 – y) (5y2 – 2 – 3y)

= 15y2 – 6 – 9y – 5y3 + 2y + 3y2

= 18y2 – 5y3 – 7y – 6

The product will be 18y2 – 5y3 – 7y – 6

(d) (4a – 3) (3a2 + 2 – 5a)

= 4a (3a2 + 2 – 5a) – 3 (3a2 + 2 – 5a)

= 12a3 + 8a – 20a2 – 9a2 – 6 + 15a

= 12a3 – 29a2 + 23a – 6

The product will be 12a3 – 29a2 + 23a – 6

(e) (5x – 1) (-2x3 + 4x – 3)

= – 10x4 + 20x2 – 15x + 2x3 – 4x + 3

= – 10x4 + 2x3 + 20x2 – 19x + 3

The product will be -10x4 + 2x3 + 20x2 – 19x + 3

(f) (2p2 – 3) (4p3 – p2 + 7)

= 8p5 – 2p4 + 14p2 – 2p3 + 3p2 – 21

= 8p5 – 2p4 – 12p3 + 17p2 – 21

The product will be (2p2 – 3) (4p3 – p2 + 7)

Question no – (3)

Solution :

(a) (x + 1) (x2 – x + 1)

= x3 – x2 + x + x2 – x + 1

= x3 + 1

The product will be x3 + 1

(b) (x – y) (x2 + xy + y2)

= x3 + x2y + xy2 – x2y – xy2 – y3

= x3 + y3

The product will be x3 + y3

Question no – (4)

Solution :

(a) (x3 – 5x2 + 2) (x2 – 2x)

= x5 – 5x4 + 2x2 – 2x4 + 10x3 – 4x

= x5 – 7x4 + 10x3 + 2x2 – 4x

The product will be x5 – 7x4 + 10x3 + 2x2 – 4x

(b) (2x2 – 3x + 4) (x2 – 5x – 3)

= 2x2 (x2 – 5x – 3) -3x (x2 – 5x – 3) + 4 (x2 – 5x – 3)

= 2x4 – 10x3 – 6x2 – 3x3 + 15x2 + 9x + 4x2 – 20x – 12

= 2x4 – 13x3 + 13x2 – 11x – 12

The product will be 2x4 – 13x3 + 13x2 – 11x – 12

Question no – (5)

Solution :

Given, (x + 2) (x2 – 6x + 8) – (2x – 3) (2x2 – x – 1)

= (x3 – 6x2 + 8x + 2x2 – 12x + 16) – (4x3 – 2x2 – 2x – 6x2 + 3x + 3)

= x3 – 4x2 – 4x + 16 – 4x3 + 8x2 – x – 3

= – 3x3 + 4x2 – 5x + 13  …(Simplified)

Algebraic Expressions Exercise 5E Solution :

Question no – (1)

Solution :

(a) 9x7/3x5

= 3x(7+5)

= 3x2         ….(Simplified)

(b) -20y12/4y8

= -5y12-8

= -5y4         ….(Simplified)

(c) -15a7/-3a15

= 5/a(15-7)

= 5/a8        ….(Simplified)

(d) 18x4y2/9x3y

= 2x(4-3)y(2-1)

= 2x1y1    ….(Simplified)

Question no – (2)

Solution :

(a) -35x8y9/-7x3y2

= 5x8-3y9-2

= 5x5y7        …(Simplified)

(b) 48a2b2c4/-12abc3

= -4a2-1b2-1c4-3

= -4abc        ….(Simplified)

(c) 10x20y7z4/0.1x16y3z9

= 10 × 10 x(20–16)y(7-3)/z9-4

= 100x4y4/z5   ..(Simplified)

(d) 0.6a4b3c2/0.3ab5c7

= 6/3 a4-1/b5-3c7-2

= 2a3/b2c5   ….(Simplified)

Question no – (3)

Solution :

(a) (3a3b) (5ab3)/(5ab) (6ab7)

= 1/2 a4b4/a2b8

= 1/2 a4-2/b8-4

= 1/2 a2/b4    ….(Simplified)

(b) 4ab(-7a3b7)/14a2b2

= 2a3b7/ab

= 2a3-1b7-1

= 2a2b6    ….(Simplified)

(c) (5a2b)2 (-100b3)/(52b)2

= – 52a4b2 × 52 × 2b3/54b2

= – 2a4b3   ….(Simplified)

(d) (-2x2y)3/(6xy2)2

= – 8x6y3/36x2y2

= – 2/9 x6-2y3-2

= – 2/9 x4y1    ….(Simplified)

(e) (3x2)3(3y)/(3x)3(3x)2

= 33x6 × 3y/33x3 × 32x2

= 1/3 x(6-5)y

= 1/3xy    ….(Simplified)

(f) (-2pq2)8/(4p2q)4

= 28p8q16/(22)4p8q4

= 28/28 q(16-4)

= q12      ….(Simplified)

Algebraic Expressions Exercise 5F Solution :

Question no – (1)

Solution :

(a) 7a + 7b by 7

7a + 7b/7

= 7a/7 + 7b/7

= a + b

(b) ax + ay by a

ax + ay/a

= ax/a + ay/a

= x + y

(c) 6y – 2 by 2

6y – 2/2

= 6y/2 – 2/1

= 3y – 1

(d) b – a by b

b – a/b

= b/b – a/b

= 1 – a/b

Question no – (2)

Solution :

(a) 8y – 8 by – 8

8y – 8/-8

= – 8y/8 + 8/8

= – y + 1

(b) 6x4 + 3x3 + 3x2 by 3x2

6x4 + 3x3 + 3x2/3x2

= 6x4/3x2 + 3x3/3x2 + 3x2/3x2

= 2x2 + x + 1

(c) 25x8 – 20x5 by 5x3y3

25x8 – 20x5/5x3y3

= 25x8/5x3y3 – 20x5/5x3y3

= 5x5/y3 – 4x2/y3

(d) x2y2z2 – xyz + 1 by xyz

x2y2z2 – xyz + 1/ xyz

= x2y2z2/xyz – xyz/xyz + 1/xyz

= xyz – 1 + 1/xyz

Question no – (3)

Solution :

(a) 35a5 + 28a4b2 – 14a3b3/ – 7a2/- 7a2

= 35a5/-7a2 + 28a4b2/-7a2 – 14a3b3/-7a2

= – 5a3 – 4a2b2 + 2ab3

(b) 16x2y – 48xy2 + 8x2y2/ 8x2y2/8x2y2

= 16x2y/8x2y2 – 48xy2/8x2y2 + 8x2y2/8x2y2

= 2/y – 6/x + 1

Question no – (4)

Solution :

Given,  x + y/y = 21

= x/y + 1 = 21

= x/y = 20

Algebraic Expressions Exercise 5H Solution :

Question no – (1)

Solution :

(a) (a + 4)2

= (a)2 + 2.a.4 + (4)2

= a2 + 8a + 16

(b) (3a + 1)2

= (3a)2 + 2.3a.1 + (1)2

= 9a2 + 6a + 1

(c) (5m + 3)2

= (5m)2 + 2.5m.3 + (3)2

= 25m2 + 30m + 9

(d) (6x + 7y)2

= (6x)2 + 2.6x.7y + (7y)2

= 36x2 + 84xy + 49y2

(e) (3ab + 2c)2

= (3ab)2 + 2.3ab.2c + (2c)2

= 9a2b2 + 12abc + 4c2

(f) (2xy + 7z)2

= (2xy)2 + 2.2xy.7z2 + (7z2)2

= 4x2y2 + 28xyz2 + 49z4

(g) (m2 + n2)2

= (m2)2 + 2.m2.n2 + (n2)2= m4 + 2m2n2 + n4

(h) (x2y + 3)2

= (x2y)2 + 2.x2y.3 + (3)2

= x4y2 + 6x2y + 9

Question no – (2)

Solution :

(a) (k – 7)2

= (k)2 – 2.k.7 + (7)2

= k2 – 14k + 49

(b) (5y – 1)2

= (5y)2 – 2.5y.1 + (1)2

= 25y2 – 10y + 1

(c) (3x – 8)2

= (3x)2 – 2.3x.8 + (8)2

= 9x2 – 48x + 64

(d) (6b – 7c)2

= (6b)2 – 2.6b.7c + (7c)2

= 36b2 – 84bc + 49c2

(e) (5mn – 2p)2

= (5mn)2 – 2.5mn.2p + (2p)2

= 25m2n2 – 20mnp + 4p2

(f) (3x2 – 4z)2

= (3x2)2 – 2.3x2.4z + (4z)2

= 9x4 – 24x2z + 16z2

(g) (5×3 – 3y2)2

= (5x3)2 – 2.5x3.3y2 + (3y2)2

= 25x6 – 30x3y2 + 9y4

(h) (9a2 – bc)2

= (9a2)2 – 2.9a2.bc + (bc)2

= 81a4 – 18a2bc + b2c2

Question no – (3)

Solution :

(a) (x + 6) (x – 6)

= (x)2 – (6)2

= x2 – 36

The product will be x2 – 36

(b) (p + 9) (p – 9)

= (p)2 – (9)2

= p2 – 81

The product will be p2 – 81

(c) (4y + 7) (4y – 7)

= (4y)2 – (7)2

= 16y2 – 49

The product will be 16y2 – 49

(d) (6x + 7y) (6x – 7y)

= (6x)2 – (7y)2

= 36x2 – 49y2

The product will be 36x2 – 49y2

(e) (3x2 – 5y) (3x2 + 5y)

= (3x2)2 – (5y)2

= 9x4 – 25y2

The product will be 9x4 – 25y2

(f) (y – x2) (x2 + y)

= (y)2 – (x2)2

= y2 – x4

The product will be y2 – x4

(g) (x2 – y2) (x2 + y2)

= (x2)2 – (y2)2

= x4 – y4

The product will be x4 – y4

(h) (a2 + bc) (a2 – bc)

= (a2)2 – (bc)2

= a4 – b2c2

The product will be a4 – b2c2

Question no – (4)

Solution :

(a) (105)2

= (100 + 5)2

= (100)2 + 2.100.5 + (5)2

= 10000 + 1000 + 25

= 11025

(b) (401)2

= (400 + 1)2

= (400)2 + 2.400.1 + (1)2

= 160000 + 800 + 1

= 160801

(c) (708)2

= (700 + 8)2

= (700)2 + 2.700.8 + (8)2

= 490000 + 11200 + 64

= 501264

(d) (98)2

= (100 – 2)2

= (100)2 – 2.100.1 + (2)2

= 10000 – 400 + 4

= 9604

(e) (199)2

= (200 – 1)2

= (200)2 – 2.200.1 + (1)2

= 40000 – 400 + 1

= 39601

(f) (10.3)2

= (10 + 0.3)2

= (10)2 + 2.10.(0.3) + (0.3)2

= 100 + 6 + 0.09

= 106.09

(g) (1.99)2

= (2 – 0.01)2

= (2)2 – 2.2 (0.01) + (0.01)2

= 4 – 0.04 + 0.0001

= 3.9601

(h) (2.1)2 + (1.9)2

= (2 + 0.1)2 + (2 – 0.1)2

= (2)2 + 2.2 (0.1) + (0.1)2 + (2)2 – 2.2.(0.1) + (0.1)2

= 4 + 0.01 + 4 + 0.01

= 8 + 0.02

= 8.02

Question no – (5)

Solution :

(a) 18 × 22

= (20 – 2) × (20 + 2)

= (20)2 – (2)2

= 400 – 4

= 396

(b) 51 × 49

= (50 + 1) (50 – 1)

= (50)2 – (1)2

= 2500 – 1

= 2499

(c) 101 × 99

= (100 + 1) × (100 – 1)

= (100)2 – (1)2

= 10000 – 1

= 9999

Question no – (6)

Solution :

(a) (298 × 298) – (205 × 205)/93

= (298)2 – (205)2/93

= (298 + 205) (298 – 205)/93

= 503 × 93/93

= 503

(b) (19.67 × 19.67) – (15.33 × 15.33)/0.434

= (19.67)2 – (15.33)2/0.434

= (19.67 + 15.33) × (19.67 – 15.33)/0.434

= 35.00 × 4.34/0.434

= 35 × 434 × 1000/434 × 10

= 3500

Question no – (7)

Solution : Area of big square = (x + 4)2

= x2 + 2.x.4 + (4)2

= x2 + 8x + 16

Area of small square = (y – 1)2

= y2 – 2.y.1 + 12

= y2 – 2y + 1

Total area of the figure,

= x2 + 8x + 16 + y2 – 2y + 1

= x2 + y2 + 8x – 2y + 17

Question no – (8)

Solution :

Area of the swimming pool, Area of the rectangle + area of the square

= (7 + x) (7 – x) + x2

= 72 – x2 + x2

= 49 sq. unit

Therefore, the area of the swimming pool will be 49 sq. unit

Next Chapter Solution :

Updated: June 19, 2023 — 1:59 pm